EXAMINATION THE PROCESS OF LONGITUDINAL SOLID WOOD PROFILE MILLING. PART I: PERFORMANCE OF CUTTER PROFILE - Gochev, Zhivko (Innovation in Woodworking Industry and Engineering design, 2014)
In this article the, process of longitudinal solid wood profile milling has been studied. In the first part of the article, an analysis is done with regard to: the profile of universal cutterhead used for experimental studies; the characteristics of the chips formation process by longitudinal milling; the influence of the feed per tooth and the accuracy of the cutter teeth placement on the quality of the processed surfaces. The conclusions will be used in the experimental investigation of the milling processes.